RANCANG BANGUN SISTEM INFORMASI PERPUSTAKAAN SMA NEGERI PINTAR RIAU BERBASIS WEB - Erzi Hidayat; Windi Taruna Agustin; Arif Rahman Hakim (Politeknik Negeri Bengkalis, 2023)
The library of SMA Negeri system is still by conventionally. It causes various problems occuring frequently. First, If the notebook is lost, the borrowing data will also belose. As a result, librarians cannot find which books were students and teachers borrowed. The second case is when the students did not find the book they were looking for, they usually asked to the librarian, but mostly the librarian did not know the arrangement of the books. So, it can be spend a long time to find the book. Based on the cases described, this research proposes to create a web-based library information system with a waterfall method and End User Computing Statistics testing. The aims of this research is to helps the librarians to manage the library data and assists students and teachers in finding books and reading books in soft file form. Based on the Black-box the system functionality has been met. Based on the End User Computing Satisfaction test by system testing by asking 12 questions, the satisfaction value of each variable is greater than 4, so the level of satisfaction is